Helicobacter pylori outer membrane vesicles directly promote Aβ aggregation and enhance Aβ toxicity in APP/PS1 mice - Dongli Meng; Yiwen Lai; Lun Zhang; Wenting Hu; Hui Wei; Cuiping Guo; Xiaopeng Jing; Huan Zhou; Rui Xiao; Liping Zhu; Shengquan Luo; Zhendong Xu; et al. (Communications Biology)
Abstract Helicobacter pylori (H. pylori) infection has been found associated with Alzheimer’s disease (AD) with unclear mechanisms. Outer Membrane Vesicles (OMVs) are spherical particles secreted by Gram-negative bacteria. Here we explore the effect of H. pylori OMVs on Aβ aggregation and toxicity. We show intraperitoneally-injected H. pylori OMVs enter the brain and co-localize with Aβ plaques in APP/PS1 mice, accompanied by aggravated Aβ pathology, exacerbated cognitive deficits and synaptic impairment, indicating that H. pylori OMVs promote β-amyloidosis and AD development. The in vitro results further identify that H. pylori OMVs significantly accelerate Aβ aggregation and increase Aβ-induced neurotoxicity. Through lipidomic analysis, we reveal that lipid components, particularly LPC 18:0 in H. pylori OMVs accelerate Aβ aggregation and enhance Aβ neurotoxicity. Moreover, H. pylori OMVs-enhanced Aβ neurotoxicity is mediated by Ca2+. These findings reveal a mechanism of H. pylori OMVs in accelerating AD development in which the bacterial OMVs-originated lipid components play a key role in promoting Aβ aggregation and neurotoxicity.